2017
DOI: 10.1002/bjs.10594
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on timing of resection of hepatocellular adenoma

Abstract: This study suggests that a 6-month cut-off point for assessment of regression of HCA larger than 5 cm to no more than 5 cm is too early. As no complications were documented during follow-up, the cut-off point in women with typical, non-β-catenin-activated HCA could be prolonged to 12 months, irrespective of baseline diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Klompenhouwer et al stated that 15% of HCA in their cohort showed regression to 50 mm or smaller after 6 months. This increased to 25% of patients after 1 year . Also, they observed that larger HCA often require more than 6 months to regress to a diameter <50 mm .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Klompenhouwer et al stated that 15% of HCA in their cohort showed regression to 50 mm or smaller after 6 months. This increased to 25% of patients after 1 year . Also, they observed that larger HCA often require more than 6 months to regress to a diameter <50 mm .…”
Section: Discussionmentioning
confidence: 96%
“…This increased to 25% of patients after 1 year . Also, they observed that larger HCA often require more than 6 months to regress to a diameter <50 mm . Their sample size allowed them to exclude a correlation between HCA subtype and response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women with large HCA (over 5 cm) [ 65 ], several solutions are available and should be discussed by a multidisciplinary tumor board: Systematic resection via surgery; Surgery after 6–12 months of estroprogestative withdrawal if HCA does not regress; Surgery only for symptomatic patients, or HCA with high risk of complications defined by molecular classification. …”
Section: Translation Into Clinical Practicementioning
confidence: 99%
“…After HCA diagnosis, lifestyle adaption with cessation of OC and weight reduction is indicated, irrespective of HCA diameter 9 . In case of growth or when the HCA fails to regress to less than 5cm, resection may be indicated 9,10 . Other indications for resection are HCA in men, patients with β‐HCA or β‐IHCA.…”
Section: Introductionmentioning
confidence: 99%